From engineer to taxi driver: Occupational skills and the economic outcomes of immigrants - Susumu Imai; Derek Stacey; Casey Warman (Queen's University, Department of Economics, 2011)
We examine the ability of male immigrants to transfer their occupational human capital using information from the O*NET and a unique dataset that includes both the last source country occupation and the first four years of occupations in Canada. We first augment a model of occupational choice and skill accumulation to derive predictions about the cross-border transferability of occupational human capital. We then test the empirical implications using the skill requirements of pre- and post-immigration occupations. We find that male immigrants to Canada were employed in source country occupations that required high levels of cognitive skills, but relied less intently on manual skills. Following immigration, they find initial employment in occupations that require the opposite. Regression analysis uncovers large returns to the quantitative skill requirements of Canadian occupations, but no returns to source country skill requirements. Finally, our empirical findings suggests that occupational skill gaps are detrimental to immigrants' earnings.
Keywords: 330; Internationale Wanderung; Einwanderung; Migranten; Qualifikation; Erwerbsstatus; Kanada